Kraniyofasiyal Ve Dentoalveoler Yapılardaki Gelişimin İskelet Olgunluk Kriterleri Dikkate Alınarak İncelenmesi - Mirzen Arat; Ayşegül Köklü; Erhan Özdiler; Meliha Rübendüz; Banu Erdoğan (Galenos Yayinevi, 1997)
In this study, facial skeletal development in pubertal spurt has been investigated in detail. The material of the study was composed of annually collected cephalometric and hand-wrist combinations of 78 individuals (43 girls and 35 boys), whose development follow-ups range from 4 to 7 years. In creating the groups, the hand-wrist films acquired with annual intervals were benefited from, and the individuals were divided into groups prepeak, peak and postpeak. The evaluation has taken into consideration the skeletal development criteria, instead of chronological age and the developmental changes of craniofacial structures were determined for each, group. The relationships between skeletal maturation and the development of facial structures were also evaluated in each study group.